Examining the relationship between board of directors' gender and sustainability disclosure - Modiba, Mantsha Emelda (University of Limpopo, 2016)
This research examined whether an improved participation of women in the board of Socially Responsible Investing (SRI) firms has any relationship with sustainability disclosure. Accordingly, the objective of this research was to examine the relationship between the number of women on the board and environmental, social and gender-employment disclosure in South African firms. The research applied a purposive sampling design to study the nine best socially responsible investing firms on the Johannesburg Stock Exchange and secondary data were collected from the sustainability reports of the firms. Using a quantitative approach, the panel-data regression analysis was used to analyse the relationship between women on the board of directors, environmental, social and gender employment disclosure. Energy consumption disclosure, social investment and the number of women employment in the firms were the proxy for environmental disclosure, social investment and gender employment disclosures respectively. Findings show a positive relationship between the number of women on the board of directors and firm disclosure on energy consumption, disclosure on women employment and social investment disclosure. However, the number of women employed in the corporate is still very low in comparison with the male counterparts. The research recommends that, given the unique social and environmental sensitivity of women, the corporate should recruit more women onto the boards to enhance accelerated corporate sustainability performance and disclosures. Key words: sustainability disclosure, women in the board, sustainability performance, energy disclosure, sustainable development
Thesis (MBA.) -- University of Limpopo, 2016
Keywords: sustainability disclosure; women in the board; sustainability performance; energy disclosure; sustainable development; Boards of directors -- United States; Boards of directors -- South Africa